Nonwoven flax fibres geotextiles effects on solute heavy metals transport in porous media. Issue 16 (15th July 2020) - Abbar, Bouamama; Alem, Abdellah; Pantet, Anne; Marcotte, Stéphane; Ahfir, Nasre-Dine; Wang, Huaqing; Ouahbi, Tariq; Duchemin, Benoît; Duriatti, Davy
ABSTRACT: Filtration tests were carried out in laboratory columns filled with crushed sand with and without flax geotextiles to study the transfer and retention of soluble heavy metals. Divalent cations of copper, zinc and lead were simultaneously and continuously injected in filtration columns. Results show that, when geotextiles discs are present the retention of metals in sand is favoured and retention profiles are modified. In addition, and unlike synthetic geotextiles, flax fibres geotextiles contribute to the retention of a significant fraction of the cationic metal pollutants in their own structure. The overall metals retention efficiency of the filter is improved. Competition between cationic metals for adsorption on retention sites occurs in the column in the order Pb > Cu > Zn. Most of the lead is retained in the inlet of the column while copper and even more zinc migrate deeper in the column. GRAPHICAL ABSTRACT: